The Effect of Glycerol Monolaurate on Intestinal Health and Disease Resistance in Cage-Farmed Juvenile Pompano Trachinotus ovatus - Huaxing Lin; Beiping Tan; Qihui Yang (Aquaculture Nutrition)
This research studied the effects of glycerol monolaurate (GML) to diets on the digestive capacity, intestinal structure, intestinal microbiota, and disease resistance for juvenile pompano Trachinotus ovatus (mean weight=14.00±0.70 g). T. ovatus were, respectively, fed six diets containing 0.00, 0.05, 0.10, 0.15, 0.20, and 0.25% GML for 56 days. The highest weight gain rate was observed in the 0.15% GML group. In the intestine, amylase activities in the 0.10, 0.15, 0.20, and 0.25% GML groups were significantly increased, compared with 0.00% GML group (P<0.05). Lipase activities in the 0.10 and 0.15% GML groups were significantly increased (P<0.05). Similar significant elevations in the protease activities were also found in the 0.10, 0.15, and 0.20% GML groups (P<0.05). Amylase activities were significantly higher in the 0.10, 0.15, 0.20, and 0.25% GML groups than that in the 0.00% GML group (P<0.05). Villus lengths (VL) and muscle thicknesses (MT) of the 0.05, 0.10, 0.15, and 0.20% GML groups were significantly enhanced, and the villus widths (VW) in the 0.05, 0.10, and 0.15% groups were significantly increased (P<0.05). Additionally, 0.15% GML significantly improved the intestinal immunity by upregulating interleukin 10 (il-10), increasing beneficial bacteria abundances (e.g., Vibrio, Pseudomonas, and Cetobacterium), downregulating nuclear factor kappa b (nf-κb) and interleukin 8 (il-8), and decreasing harmful bacteria abundances (e.g., Brevinema and Acinetobacter) (P<0.05). After challenge test, GML significantly increased the survival rate (80%–96%) (P<0.05). In addition, ACP and AKP activities in the GML-supplemented groups were significantly higher than those in the 0.00% GML group, and LZM activity was significantly higher in the 0.05, 0.10, 0.15, and 0.20% GML groups than that in the 0.00% GML group (P<0.05). In summary, 0.15% GML significantly promoted the intestinal digestibility, improved the intestinal microflora, regulated intestinal immune-related genes, and increased resistance to V. parahaemolyticus of juvenile pompano T. ovatus.